Slogan Back to the Quran and Sunnah: Studi Pemikiran Jamaluddin al-Afghani - Syahuri Arsyi (Matan : Journal of Islam and Muslim Society, 2021)
This study aims to discuss the thoughts of Jamaluddin al-Afghani (1839-1897), one of the reformers of Islamic modernism in the 19th century. This research is a literature study with a factual-historical approach to find out the flow of al-Afghani's thought development, whether related to the environment or the influences experienced in the course of his thought. The results showed that al-Afghani's Islamic political movement is very unique and different from the others. The movement is carried out with the frame of the slogan "back to the Quran and Sunnah" as a response to the attitude of Muslims who are experiencing the decline, and a response to western imperialism in the Islamic world and encourages Muslims to unite under one umbrella called Pan-Islamism. Al-Afghani used the slogan "back to the Quran and Sunnah" in his political movement as a form of enthusiasm for Muslims to do ijihad on Islamic teachings, especially the concepts of qadla 'and qadar which are often misunderstood so that it results in Muslims Islam is trapped in a fatalism and static attitude.